The future of health in Zimbabwe - Kidia, Khameer K. (Glob Health Action, 2018)
In November 2017, following a military intervention, Robert Mugabe was forced to resign as president of Zimbabwe – where he had ruthlessly ruled since 1980. Mugabe’s regime was responsible for destroying the country’s excellent health system. I argue that this is a unique moment for health reform in Zimbabwe. This reform should focus on three areas: (1) repairing relationships with the international community by focusing on human rights and eliminating corruption, (2) strengthening the health workforce through retention strategies, training, and non-specialist providers, and (3) community engagement. The future of Zimbabwe’s health system is in limbo, and now is a unique opportunity to make positive change.